2020
DOI: 10.3389/fpsyg.2020.576771
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System and Recall Modeling in Audiovisual Emotion-Mediated Advertising Using Partial Least Squares-Path Modeling

Abstract: Interest in improving advertisement impact on potential consumers has increased recently. One well-known strategy is to use emotion-based advertisement. In this approach, an emotional link with consumers is created, aiming to enhance the memorization process. In recent years, Neuromarketing techniques have allowed us to obtain more objective information on this process. However, the role of the autonomic nervous system (ANS) in the memorization process using emotional advertisement still needs further research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Our results showed that DFA α 1 as a non-linear index of HRV did not distinguish the different affective image regimes under ultra-short recordings. Although previous work showed that there can be differences in HRV measures when comparing neutral and arousing sessions ( Valenza et al, 2012 ) or watching positive and negative videos ( Barquero-Pérez et al, 2020 ; Ghiasi et al, 2020 ), our findings are consistent with other works that showed the linear HRV metric RMSSD did not distinguish between positive and negative emotions using IAPS ( Schippers et al, 2018 ), and non-linear HRV metric DFA α 1 did not distinguish different emotionally arousing settings ( Marín-Morales et al, 2021 ). We hypothesize that because pure regime participants knew to expect images of the same type, there may not have been a sufficient change in emotional context to create significant variation in their heart rate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that DFA α 1 as a non-linear index of HRV did not distinguish the different affective image regimes under ultra-short recordings. Although previous work showed that there can be differences in HRV measures when comparing neutral and arousing sessions ( Valenza et al, 2012 ) or watching positive and negative videos ( Barquero-Pérez et al, 2020 ; Ghiasi et al, 2020 ), our findings are consistent with other works that showed the linear HRV metric RMSSD did not distinguish between positive and negative emotions using IAPS ( Schippers et al, 2018 ), and non-linear HRV metric DFA α 1 did not distinguish different emotionally arousing settings ( Marín-Morales et al, 2021 ). We hypothesize that because pure regime participants knew to expect images of the same type, there may not have been a sufficient change in emotional context to create significant variation in their heart rate.…”
Section: Discussionsupporting
confidence: 91%
“…These changes in the successive heartbeats are an integral component of physiological research and are becoming more standardized in the field ( Laborde et al, 2017 ; Berntson et al, 1997 ; Malik, 1996 ) to provide diagnostic information in certain medical conditions ( Yeh et al, 2009 ; Gronwald et al, 2019 ) and insights into the parasympathetic nervous system ( Malik, 1996 ). Past studies have shown that shifts in HRV can be induced by a variety of different types of affective stimuli such as watching positive and negative videos ( Barquero-Pérez et al, 2020 ; Ghiasi et al, 2020 ), the Cold Pressor Stress Test ( Ghiasi et al, 2018 ; Ghiasi et al, 2020 ), and imagining scenarios which evoke an emotional response ( McCraty et al, 1995 ). Using these different affective induction techniques, researchers have proposed various models to measure changes in the autonomic nervous system in reaction to an affective stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological techniques, for example, ET can measure visual attention such as fixation, pupil dilation, eye movements [19]. GSR and ECG can measure emotional arousal (e.g., high/low) and heart rate [20]. EMG can only measure the unconscious responses of the emotional valence (e.g., pleasure/displeasure, sadness/excitement, and forth) [21].…”
Section: Neuromarketing Tools Used In Studying Consumers' Behavior To...mentioning
confidence: 99%
“…The GSR is used to gauge the sweating level and ECG to measure the heart rate/heartbeat [77]. ECG can record the heartbeat activations during exposure to marketing stimuli [20]. Heart rate is considered a good scale of emotional valence, wherein the heartbeat's slowing down in the short term is associated with positive and negative emotions.…”
Section: Neuromarketing Tools Used In Studying Consumers' Behavior To...mentioning
confidence: 99%
See 1 more Smart Citation